Utilization of The Internet as an Educational Tool in the Punggur Kecil Village: Pemanfaatan Internet Sebagai Sarana Edukasi Di Desa Punggur Kecil - Hasfani, Hirzen; Irma, Irma Nirmala; Rahmi, Rahmi Hidayati; Suhardi, Suhardi (Institut Riset dan Publikasi Indonesia, 2024)
Internet, as a global computer network, plays a crucial role in connecting local and regional networks worldwide. This network offers various functions, including communication, information access, e-commerce, entertainment, and education. In Punggur Kecil Village, Kubu Raya Regency, West Kalimantan Province, the implementation of the internet has provided significant benefits such as improved information access, new business opportunities, expanded social connections, and a learning resource for the village community. Education is a fundamental pillar in building an advanced and educated village, as it enhances the skills and knowledge of the residents. However, most villagers still primarily use the internet for entertainment. To optimize the use of the internet as an educational medium, training and outreach are effective strategies. One proposed approach is video creation training using the CapCut application, aimed at improving the digital skills of the villagers. This training is expected to help them utilize the internet more productively, enrich their knowledge, and broaden their insights into the potential of digital technology.